Taxing human capital efficiently: the double dividend of taxing non-qualified labour more heavily than qualified labour - Wolfram F. Richter (Institute for the Study of Labor (IZA), 2006)
Assuming decreasing returns to education and the endogenous supply of qualified and non-qualified labour it is shown to be efficient to supplement a consumption tax with positive incentives for education. If the return from education is isoelastic and if the choice is between (i) subsidizing the monetary cost of education and (ii) taxing non-qualified labour income more heavily than qualified labour income while keeping the effective cost of education constant, the latter policy is shown to be second-best efficient. In particular, any tax distortions should be constrained to labour choices while the choice of education should remain undistorted. The result holds for arbitrary utility functions.
urn:nbn:de:101:1-20090825364
Keywords: 330; Bildungsverhalten; Lohnsteuer; Optimale Besteuerung; Qualifikation; Doppelte Dividende; Theorie